Conciencia fonológica y su relación con la escritura en niños de 5 años de las I.E.I de la zona urbano Marginal del distrito de Rioja - Morí Leovina, Tanchiva (2012)
The research aimed to determine the relationship of phonological awareness with writing for children 5 years of educational institutions in the initial level of marginal urban area of Rioja district in 201 O, was aimed at checking that phonological awareness more writing in children. The empirical data was collected from 26 children, using two data collection instruments a test of phonological awareness and writing test. The hypothesis testing was performed by comparing the correlation coefficient with the parameters set, considering that phonological awareness is more writing when the coefficient ls positive, as well as to phonological awareness there is less writing when the coefficient is negative . . In the analysis of results has been fmmd that the highest percentage, represented by 46.15% have moderate phonological awareness, in addition, most children had very high level in writing, represented by 34.62%. The relationship between phonological awareness and writing is explained by the Pearson correlation coefficient, which reached a value is 0.83, according to this value, there is a strong positive correlation, therefore, to greater phonological awareness in children writing 5 years of the lnitial Level Educational lnstitutions in the Urban Area of District Marginal Rioja.